Alternatives to the use of fire in agriculture as a way to mitigate burning in the Amazon (Research, Society and Development, 2020)
In the Amazon, most different types of soil are poor, so the smallholder depends on burning the accumulated biomass (cutting and burning) to increase the nutritional qualities of the soil and prepare the area for cultivation using ash, which it can, for example, greatly increase the amount of potassium, calcium and magnesium available in the soil. The present work aims to present less aggressive alternatives to Amazonian ecosystems with regard to the traditional slash and burn system widely used by farmers throughout Brazil. A bibliographic review on the topic was carried out in scientific academic journals available online and in print, bringing together alternatives for the use of fire found in the consultation sources. The techniques of preparing the soil without the use of fire seek mainly to eliminate uncontrolled burning and to recover the fertility of the soil thus allowing the continuity of the productive activity without great risks and impacts to the local ecosystem. Therefore, the use of technologies and management methods that can somehow mitigate the incidence of burning in the Amazon is essential for the sustainable development of the productive activities developed in this biome.